Cognitive performance in former professional football (soccer) players is affected by estimated heading frequency. (31st December 2021) - Bruno, Davide; Rutherford, Andrew
Abstract: Background: The link between football (soccer) heading and/or head injury is a concern given the popularity of football worldwide. To assess this link, memory ability of former professional footballers (FPFs) was tested, and self‐reported data on positions played, previous head injuries, and frequency of headers were obtained. Method: Data were collected by post from 60 male FPFs who had played for teams in England. Each individual received a questionnaire requiring them to self‐report: demographics data; information on playing career, including playing position; information on number of head injuries sustained in training and match play; and an estimate of how many headers they normally took in training and match play. Additionally, the Test Your Memory (TYM) self‐administered memory test also was included. FPFs mean age was 67.5 (9.5), ranging from 39 to 87. Result: Bayesian and traditional (frequentist) regression analyses were carried out using the TYM score as outcome (continuous and binary). Age and estimated non‐football head injuries served as covariates (null model). Predictors were playing position, estimated career head injuries, and estimated career headers. As playing position influences likelihood of heading the ball, a rating score was co‐designed with FPFs ranging from 1 (not likely, e.g., goal‐keeper) to 5 (most likely, e.g., centre‐forward). The results of our analyses showed across all tests that estimated career headers, but not playing position or estimated career head injuries, were associated with the overall cognitive outcome. We calculated from our data that the TYM score declined by about 3 points for each 100, 000 career headers reported. Conclusion: This is the first study, to our knowledge, to provide evidence in former professional football players that heading the ball may impact cognitive ability.